Traumatic superior orbital fissure syndrome: a rare case report - Eskitascioglu, Teoman; Yontar, Yalcin; Aydin, Ahmet; Tucer, Bulent (The European Research Journal, 2017)
Superior orbital fissure syndrome is a severe clinical entity characterized by injuries of neurovascular structures passing through the superior orbital fissure. A 38-year-old male patient admitted to outpatient clinic with left upper eyelid ptosis, ecchymosis, mydriasis, hypoesthesia in upper eyelid and frontal region, blepharoptosis, restriction of ocular movements in all directions, loss of accommodation reflex and absence of direct pupillary reflex. Three-dimensional computed tomography scans demonstrated left-sided orbital fractures resulting in obliteration of the superior orbital fissure. He underwent surgical decompression. The patient had intravenous methylprednisolone administration at preoperative and postoperative periods during hospitalization. He was discharged on the postoperative day 5. At the 9th postoperative month, the cranial nerve functions were almost completely recovered. We consider that the decompressive surgery in conjunction with perioperative steroid therapy may be effective for the traumatic superior orbital fissure syndrome.